Prevalence and genetic basis of extended-spectrum β-lactamase-producing Escherichia coli carriage in broiler farms in the United Arab Emirates - Khalifa, Hazim O.; Mohammed, Temesgen; Elbediwi, Mohammed; Abdalla, Afra; Mohamed, Mohamed-Yousif Ibrahim; Ramadan, Hazem; Lakshmi, Glindya Bhagya; Ghazawi, Akela; Habib, Ihab (Frontiers in Veterinary Science, 2025)
BackgroundPoultry production plays a vital role in ensuring food security and nutritional sustainability in the United Arab Emirates (UAE). However, the emergence and spread of antimicrobial-resistant bacteria in poultry farms present a growing public health concern in the region. To address this gap, this study investigated the prevalence and genetic basis of extended-spectrum β-lactamase (ESBL)-producing Gram-negative bacteria in cecal contents of chickens collected from two major poultry farms in Al Ain, UAE.MethodsA total of 77 samples were collected over an eleven-month period, yielding 146 non-duplicate Gram-negative isolates, of which Escherichia coli was the most prevalent species (82.9%). All the isolates were tested phenotypically and genotypically by PCR and whole genome sequencing for different resistance mechanisms.ResultsPhenotypic characterization revealed high rates of ESBL production (87.7%), with 95% of E. coli isolates exhibiting this trait. Antimicrobial susceptibility testing indicated high resistance among β-lactam antibiotics, with ampicillin (100%), ceftriaxone (91.1%), cefoperazone (89%), and cefoxitin (48.6%), while resistance to amoxicillin-clavulanic acid (10.3%), meropenem (0%), and imipenem (0%) was notably lower. Overall resistance rates were also high for quinolones (89%), tetracycline (72.6%), and chloramphenicol (41.1%). The genotypic analysis identified blaTEM (78.1%) and blaCTX−M (76.7%) as the most common resistance genes, with blaCTX−M−1 group being predominant. Whole-genome sequencing of selected isolates confirmed the presence of blaCTX−M−55, blaCTX−M−15, and blaCTX−M−8 as major genes contributing for ESBL production along with various other resistance and virulent determinants. Notably, 10.3% of isolates harbored the mcr-1.1 gene, indicating colistin resistance. WGS-based sequence typing revealed 19 distinct sequence types (STs), with ST694 being the most prevalent, followed by ST10 and ST155. Several isolates, such as ST162 and ST10 were recovered from different farms, suggesting possible dissemination across poultry production sites. Phylogenetic analysis revealed that the multidrug-resistant E. coli lineages identified in this study were highly related to isolates recovered from humans and chicken carcasses in the UAE, indicating possible transmission events within and between poultry farms.ConclusionOur findings underscore the potential zoonotic risk posed by these strains and highlight the urgent need for strengthened antimicrobial stewardship, enhanced biosecurity practices, and continuous surveillance to limit the spread of resistant bacteria in poultry production and protect public health.